2004
DOI: 10.1063/1.1645511
|View full text |Cite
|
Sign up to set email alerts
|

Sodium diffusion through amorphous silica surfaces: A molecular dynamics study

Abstract: We have studied the diffusion inside the silica network of sodium atoms initially located outside the surfaces of an amorphous silica film. We have focused our attention on structural and dynamical quantities, and we have found that the local environment of the sodium atoms is close to the local environment of the sodium atoms inside bulk sodo-silicate glasses obtained by quench. This is in agreement with recent experimental results.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 62 publications
1
6
0
Order By: Relevance
“…During shear deformation, the network modifier (Na atoms) appears to be the most mobile atomic species, followed by oxygen and silicon atoms. This order respects as well the mobility observed by thermal activation [71][72][73]. It appears that reducing the free volume in the structure (by compressing the samples) reduces the global mobility of the atoms.…”
Section: A Nonaffine Displacementssupporting
confidence: 68%
“…During shear deformation, the network modifier (Na atoms) appears to be the most mobile atomic species, followed by oxygen and silicon atoms. This order respects as well the mobility observed by thermal activation [71][72][73]. It appears that reducing the free volume in the structure (by compressing the samples) reduces the global mobility of the atoms.…”
Section: A Nonaffine Displacementssupporting
confidence: 68%
“…Above 300°C, a loss of NBO with a consequent increase in BO is detected; this could be attributed to the condensation of NBOs to BO upon desorption of modifier ions (Figure A). While a loss in NBO is observed on the unleached surface, there is an increase in NBO on the leached surface due to out‐diffusion of sodium (Figure B) . The formation of new NBO sites on the leached glass due to sodium out‐diffusion is not explicitly evident in the O 1s spectrum of the leached glass at 500°C in Figure because its quantity is so small.…”
Section: Resultsmentioning
confidence: 94%
“…| 649 diffusion of sodium ( Figure 2B). 26,27 The formation of new NBO sites on the leached glass due to sodium out-diffusion is not explicitly evident in the O 1s spectrum of the leached glass at 500°C in Figure 3 because its quantity is so small. Other researchers have shown that sodium inclusion into a silica network results in creation of NBO sites similar to those in sodium silicate glasses.…”
Section: Xps Quantificationmentioning
confidence: 99%
“…46,47 In other words, lithium ions are more susceptible to diffuse toward the nearest most constrained Si− O−Si bonds, which are the most reactive sites in the silica network, than Na + and K + ions. 48 However, diffusion parameters are not the only ones to be taken into account. Indeed, Mazzara et al well described that creation of a nonbridging oxygen is accompanied by the rearrangement of silica tetrahedra surrounding the diffusing ion in a defined stereochemical order, 49 highlighting that relaxation of the amorphous silica network around the ion and finally the film densification is the combination of the creation of nonbridging oxygen atoms and also the steric effect of the diffusing cations.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…46,47 In other words, lithium ions are more susceptible to diffuse toward the nearest most constrained Si-O-Si bonds, which are the most reactive sites in the silica network, than Na + and K + ions. 48 However diffusion parameters are not the only ones to take into account. Indeed Mazzara et al well described that creation of a nonbridging oxygen is accompanied by the rearrangement of silica tetrahedra surrounding the diffusing ion in a defined stereochemical order.…”
Section: ) Sio 2 Mesopore Reconstruction Using Lithium or Potassium Ionsmentioning
confidence: 99%